2022
DOI: 10.3389/fcimb.2022.873989
|View full text |Cite
|
Sign up to set email alerts
|

Wildlife and Antibiotic Resistance

Abstract: Antibiotic resistance is a major human health problem. While health care facilities are main contributors to the emergence, evolution and spread of antibiotic resistance, other ecosystems are involved in such dissemination. Wastewater, farm animals and pets have been considered important contributors to the development of antibiotic resistance. Herein, we review the impact of wildlife in such problem. Current evidence supports that the presence of antibiotic resistance genes and/or antibiotic resistant bacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
57
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 80 publications
(89 reference statements)
2
57
0
Order By: Relevance
“…and Salmonella enterica , by the interaction with wild small mammals (Lovera et al, 2017; Ribicich et al, 2010). Our present findings support that these wild small mammals could be important not only in the pathogen transmission on farms but also in the transmission and maintenance of antimicrobial‐resistant microorganisms (Laborda et al, 2022). In the last years, small mammals have been considered as vectors and reservoirs of antimicrobial‐resistant microorganisms, favouring the dissemination of AMR in the environment (Ong et al, 2020).…”
Section: Discussionsupporting
confidence: 88%
“…and Salmonella enterica , by the interaction with wild small mammals (Lovera et al, 2017; Ribicich et al, 2010). Our present findings support that these wild small mammals could be important not only in the pathogen transmission on farms but also in the transmission and maintenance of antimicrobial‐resistant microorganisms (Laborda et al, 2022). In the last years, small mammals have been considered as vectors and reservoirs of antimicrobial‐resistant microorganisms, favouring the dissemination of AMR in the environment (Ong et al, 2020).…”
Section: Discussionsupporting
confidence: 88%
“…The low rate or lack of Wolbachia infection in the cockroaches may change in future because it is shown that changing the gut microbiota composition with antibiotic treatment enhanced Wolbachia density in Drosophila melanogaster [ 58 ]. We have no evidence to assess the impact of antibiotic treatment on the incidence and frequency of Wolbachia in German cockroaches, however, cockroaches are exposed to antibiotics in places such hospitals [ 59 , 60 ] and most bacterial agents isolated from cockroaches are antidrug-resistant and antibiotic-resistant [ 61 ]. These situations provide cockroaches with diverse antibiotic treatments which may result in raising Wolbachia density in future and could be the subject of future studies.…”
Section: Discussionmentioning
confidence: 99%
“…So far, it appears that the emergence of AMR occurs under selection, mostly by antibiotics, however other components, such as heavy metals or biocides, may also play a role in the development of antimicrobial resistance. As a result, the presence of clinically relevant antimicrobial resistant genes and antibiotic-resistant bacteria in wild animals that are not getting antibiotics should be seen as a sign of antimicrobial resistant pollution [100][101][102].…”
Section: Discussionmentioning
confidence: 99%